INCOME TAX ALLOCATION. - Graham, Willard J. (The Accounting Review, 1959)
Abstract This article focuses on the subject income tax allocation. The first important pronouncement on this subject was made in 1944 by the Committee on Accounting Procedure of the American Institute of Certified Public Accountants. The most convincing case for income tax allocation rests upon its proper matching of expense with revenue, the allocation of income tax expense among periods in relation to the reported net income rather than the taxable income. While the income statement does report the results of past operations, its utility to the reader depends primarily upon its validity as a basis for appraising the profitability of, or planning the control of-future operations. The reduction in income tax which results from additional depreciation deductions for tax purposes, in excess of depreciation recorded in the accounts, should not, be considered an immediate saving in expense to be reflected in current income. It may be noted in passing that in the area of public utility rate-making the recognition of deferred credits to income tax expense is currently a burning issue. Where public utility companies use declining amount depreciation for tax purposes only, the failure of commissions to recognize such deferred credits and to grant some return thereon for rate purposes results in a sort of government subsidy to consumers of public utility services.